HEMIANOPSIA HOMONIM SEBAGAI GEJALA TUNGGAL PADA PASIEN STROKE - Gracia Meliana Tanoyo, AABN Nuartha (NEURONA, 2015)
STROKE SIGNS AND SYMPTOMS MAY VARY DEPENDING ON THE BRAIN AREA THAT IS AFFECTED POSTERIOR CIRCULATION STROKE ARE RARE COMPARED TO ANTERIOR CIRCULATION SITE PATIENTS MAY COME WITH VISUAL PROBLEMS COMPLAINT ONLY MAKING CLINICIANS UNAWARE OF STROKE AS THE DIAGNOSIS WE REPORT 2 STROKE CASES PRESENTS ISOLATED HOMONYMOUS HEMIANOPSIA PATIENTS WHO COME WITH SUDDEN VISUAL IMPAIRMENT INCLUDING ISOLATED HOMONYMOUS HEMIANOPSIA AND ARE ASSOCIATED WITH VASCULAR RISK FACTORS HYPERTENSION DIABETES MELLITUS DISLIPIDEMIA SMOKING ALCOHOL CONSUMPTION ETC SHOULD BE SUSPECTED AS STROKE PATIENT UNTIL PROVEN OTHERWISE